Navigating Conflict Towards Innovation: Exploring the Role of Supervisor Support - Permatasari, Mezaluna Indy; Herachwati, Nuri; Mudzakkir , Muhammad Fakhruddin; Pujianto, Wahyu Eko; Yogatama, Gandi Aswaja; Nadia, Fiona Niska Dinda (Universitas Airlangga, 2025)
Objective: This study purposefully analyses innovative work behaviour that is directly or indirectly influenced by task conflict through constructive conflict mediation, with supervisor support for innovation as a moderator. Design/Methods/Approach: The study participants consisted of 333 employees working in the R&D and Marketing divisions of eight subsidiaries of the food and beverage industry. Hypothesis testing using AMOS as software for SEM. Findings: This study showed that there was a positive and significant effect of task conflict on innovative work behavior. In addition, task conflict also had a positive and significant effect on constructive conflict. Furthermore, constructive conflict mediates the relationship between task conflict and innovative work behavior. However, this study found no significant moderating effect of supervisor support for innovation in the relationship between constructive conflict and innovative work behavior. Originality/Value: This study contributes to the existing literature on Constructive Controversy Theory by exploring the relationship between task conflict and innovative work behavior, while uniquely analyzing the mediating role of constructive conflict and the moderating role of supervisor support on innovation, aspects that have not been fully addressed in previous studies. Practical/Policy implication: These findings have implications for organizations to encourage constructive conflict optimally to enhance innovative work behavior. Organizations should encourage employees to manage conflict effectively by applying the principles of constructive conflict. HR managers of food and beverage companies seeking to increase employees’ innovative work behavior should be able to manage task conflicts constructively through open discussions that can produce new solutions.